PENDAMPINGAN OLIMPIADE SAINS NASIONAL BIDANG EKONOMI BERBASIS PARTICIPATORY TRAINING AND MENTORING DI SMA NEGERI - Firman Rato Risky; Hijrasil; Agatha Christy Situru; Rusandry Rusandry; Syahrial Maulana Maulana; Mahardika Catur Putri Wana; Zandy Pratama Zain (Universitas Bangka Belitung, 2026)
The National Science Olympiad (OSN) in Economics is a platform for developing academic competence that demands critical thinking, analytical, and problem-solving skills. However, some students still struggle to grasp the nature of the subject matter and the specific types of questions featured in the competition. This community service initiative aims to enhance the academic competence and preparedness of students from SMA Negeri 1 Ternate City for the Economics OSN using a Participatory Training and Mentoring (PTM) approach. The program was conducted over three months across 12 sessions, comprising conceptual reinforcement, discussions, case study analyses, practice questions based on Higher Order Thinking Skills (HOTS), competition simulations, and evaluations. The results indicate improvements in the participants' understanding of the material, analytical problem-solving abilities, active learning engagement, and self-confidence. The PTM approach fostered active student involvement through collaborative and problem-solving-based learning. Consequently, the program effectively enhanced the participants' readiness for the Economics OSN and holds potential as a mentoring model applicable to other schools.